Line let loose : scribbling, doodling and automatic drawing - Maclagan, David, 1940- (Reaktion, 2014)
Maclagan shows that each of the marginal forms of drawing -- scribbling, doodling, and automatic drawing -- has its own history in spiritualism, surrealism, abstract expressionism, and psychedelic art and considers their new relationship to twenty-first-century digital culture.